LITHIUM-ION BATTERY PERFORMANCE SIMULATION DURING THE DISCHARGE PROCESS VIA SINGLE PARTICLE MODEL APPROACH - Aryo Kristianto, Sigit
Research of lithium ion battery (LIB) performance based on simulation has been carried out to calculate and optimize the battery performance parameters such as battery capacity, working potential, and discharge time. The simulation is carried out using electrochemical models, namely the Single Particle Model (SPM). This model’s approach comes by observing the lithium diffusion process between the spherical electrode particles through a separator. From the SPM model, a simple mathematical equation has been derived that describes the electrochemical process that occurs inside the battery and also used to calculate the output of battery performance such as battery capacity, discharge time, and battery potential. Calculations are performed quickly on simple software such as Excel without reducing the accuracy of the output. Mathematical equations in the model gives profiles of lithium concentration, electrolyte concentration, and potential at the electrodes, as well as battery working potential compared to the battery capacity. The LIB type with LMO cathode in a pouch-cell was chosen as the initial reference for simulating battery performance. The calculation of the lithium concentration at the electrode gives value of the lithium concentration at the anode to decrease and the lithium concentration at the cathode to increase during the discharge process. The increase in the discharge current parameter in this calculation gives smaller discharge time value and lower battery capacity value (421s and 1.169 mAh.cm-2 at 0.01 mA.cm-2), while decreasing the discharge current value gives a higher time value. larger and larger rated battery capacity (13,360s and 1.855 mAh.cm-2 at 0.0005 mA.cm-2). The calculation of the electrolyte concentration at the electrode shows a change in the value of the electrolyte concentration at the electrode to only occur during the initial discharge period and do not change towards the end of the discharge period. In the calculation of the current and potential of the electrode, there is an increase in the value of the overpotential and potential drop as the value of the discharge current parameter increase. For the calculation of potential and battery capacity, variations in the value of the lithium concentration parameter give higher capacity values and similar battery voltages (~ 4.0V at 0.014 – 0.016 mol.cm-3).